A Comparison of CBM-WE Scoring Metrics and Progress Monitoring Frequency Among Second-Grade Students. Issue 3 (14th September 2020) - Hier, Bridget O.; January, Stacy-Ann A.; Van Norman, Ethan R.
Abstract: This study examined the effect of progress monitoring frequency and scoring metric on curriculum-based measurement of written expression (CBM-WE) progress monitoring estimates. The writing progress of 116 second-grade students receiving a classwide writing fluency intervention in their general education classrooms was monitored across 13 weeks (i.e., 1 week of baseline and 12 weeks during the intervention) using CBM-WE. The writing samples were scored for total words written, words spelled correctly, correct writing sequences, and correct minus incorrect writing sequences. Repeated measures analyses of variance (ANOVAs) revealed that progress monitoring frequency (weekly, bimonthly, monthly, or every 6 weeks) had a small effect on intercept and slope but a moderate effect on standard error of the estimate ( SEE ) and standard error of the slope ( SEb ). Scoring metric had a moderate effect on intercept but a small effect on slope, SEE, and SEb . Students' intercepts were not related to their slopes across any scoring metrics. Overall, the results of this study suggest that monitoring students' writing progress every 6 weeks may reduce error while preserving their intercept and slope estimates.